Study on Inhibitory Effect of Cavity on Gas Explosion Propagation. (13th January 2021) - Yan, Zhuo; Yuan, Shujie; Li, Zhongqing; Gu, Shicheng; Mu, Chaomin
Abstract : It is pointed out in the literature that the vacuum chamber has the effect of explosion suppression. The effect of explosion suppression depends on the volume of the vacuum chamber, while the vacuum degree has little effect on the performance of explosion suppression. Inspired by this, to explore a new method of gas explosion suppression, a rectangular steel cavity with a wall thickness of 10 mm, a length of 500 mm, a width of 800 mm, and a height of 200 mm was designed. The cavity was installed in a pipeline system to carry out experimental research and to investigate the law of attenuation of gas explosion flames and shock wave overpressure after passing through the cavity. The results show that the single cavity has the function of flame-out and wave attenuation, which attenuates the explosion flame and shock wave overpressure by 42.5% and 11%, respectively, and that the dual cavity further improves the performance of flame-out and wave attenuation, which attenuates flame and shock wave overpressure by 75.4% and 26.7%, respectively. On the basis of the experimental study, a numerical model was established, and a numerical simulation was carried out under the same conditions as the experimental study. The results show that the single cavity inhibits the propagation of the shock wave and attenuates the shock wave overpressure by 10.61%. The dual cavity further improves the suppression performance and attenuates the shock wave overpressure by 28.88%. Finally, by simulating the propagation process of the gas explosion shock wave and flame in the cavity, the mechanism of inhibiting gas explosion propagation by the cavity structure is analyzed.